Influence of Vanadium and Chromium Addition on Morphology and Composition of Iron Based Phases in AlSi10MgMn Alloy - Maria Zihalova; Dana Bolibruchova; Dalibor Vojtech (Communications - Scientific letters of the University of Zilina, 2015)
Application of secondary Al-Si alloys is mostly influenced by amount of impurities. Detrimental effect of iron, as the most harmful impurity, refers mainly to morphology of iron intermetallic phases. Morphology of iron phases can be influenced by several methods from which the most common is addition of some elements. In primary alloys manganese is commonly used, but its influence is not such favourable in high iron levels because of so-called sludge phase formation. Higher iron content thus requires other alloying elements which can be vanadium, chromium or others. In this article, vanadium and mutual vanadium and chromium influence on iron phase morphology and chemical composition is analysed by optical microscopy, SEM observations and EDX analysis.